Tafsir Ideologis dalam Khazanah Intelektual Islam - Zamzami, M. Subhan (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2014)
One of the causes is not the end of the study the Koran is the Koran contains many possible meanings (Wujûh al-Ma‘ânî) continuous potential can be explored and interpreted in accordance with the methods and tendencies interpreter. Therefore, no wonder the result was rich in meaning and interpretation is different, so lure the attention of others to re-refine and refuse to offer a different perspective. This viewpoint difference is attributed to the possibility of the many meanings of the Koran, also due to socio-cultural and areas of specialization of each interpreter. Ideology and political upheaval Muslims initial period stimulate the birth of the leaders of rival political and theological thinking bolder and varied. As evidence, if at the time of the Prophet and the Companions interpretation of verses mutashâbih tend to be avoided, the interpretation of later generations of the same paragraph as the focus of their attention and more wide open. So also with the interpretation of the Koran political interests and ideological bias increasingly widespread